The role of energy policy in agricultural biogas energy production in Visegrad countries - Chodkowska-Miszczuk Justyna; Kulla Marián; Novotný Ladislav (Bulletin of Geography. Socio-Economic Series, 2017)
Energy production by agricultural biogas plants has recently recorded considerable growth in Visegrad countries. The development was enhanced by European Union’s efforts to increase the proportion of energy produced from renewable sources. The paper aims to assess the role of energy policy in the development of agricultural biogas energy production in Visegrad region. Conducted studies have shown that among various forms of support for energy production from renewable energy sources, the price system prevails, including the support by feed in tariffs and bonuses. Feed in tariffs were adopted in Czech Republic, Hungary and Slovakia. Another kind of support system – a quota system – was adopted in Poland, what includes tendering and certificate systems. The results confirm the adoption of legal framework was necessary step to enable agricultural biogas energy production in Visegrad countries, but itself it was not enough to stimulate development of agricultural biogas energy production significantly. Rapid development in each country was recorded only after the certain financial support systems took effect, what made production of agricultural biogas energy economically efficient for investors. The production of energy from agricultural biogas grew the most in the Czech Republic and Slovakia, where the financial support was the highest. Nevertheless, the protracted process of changes in legal framework and transformation of energy policy, certain measures including state-controlled price-making systems, risk regarding with auction system might hamper agricultural biogas energy production further development.